TYPES OF FEEDBACK APPEAR IN TEACHING-LEARNING PROCESS AT SMA 1 MUARO JAMBI - Raju Kurniawan (Prologue: Journal on Language and Literature, 2024)
This qualitative research aimed to investigate frequently types of feedback in learning and teaching process at Senior High School 1 Muaro Jambi. Data were collected through classroom observation in video recording learning and teaching process. The participant of this research is 11th MIPA 1 Grader of Senior High School 1 Muaro Jambi. The observation data analyzed descriptively using discourse analysis through conversation analysis. Based on the research result, there were several types of feedback appear in classroom activities such as direct feedback and indirect feedback. Indirect feedback modified became a several part such as Feedback, which happened at a literal level become to comprehend or to request what the utterance meant the statement was wrong, High or low intonation feedback speeches either questions or statement that high intonation referred the statement was wrong or low intonation refers right and One of kind of Feedback, which was speaker paraphrase utterance’s statement or question to substitute utterance’s wrong statement recast. As suggestion, Second language learner (L2) learner and teacher could identified and applied the feedback in classroom activities.